CLINICAL EVALUATION OF COMPLICATIONS DURING PROSTHESIS WITH INDIRECT RESTORATIONS FOR FRONT TEETH - V.V. Chamata (Український стоматологічний альманах)
The esthetic appeal, durability, and biocompatibility of porcelain laminate veneers (PLVs) have made them an established option for restoring anterior teeth for almost three decades. Today, PLVs are mainly used to optimize tooth form and position, close diastemata, replace discolored or unesthetic composite resin restorations, restore teeth with incisal abrasions or tooth erosion, and mask or reduce tooth discoloration. They are a valid alternative to complete-coverage restorations since they avoid aggressive dental preparation, thus maintaining tooth structure. However, even such high-precision restorations have a failure rate and complications that are detailed in this article. The least common problems associated with porcelain laminate veneers are marginal discoloration and loss of color stability. A possible cause of marginal discoloration and the loss of color stability of the restoration is marginal leakage or a breakdown of the bond either between the cement and the tooth or between the cement and the veneer. This discoloration starts as a dark line but eventually works its way under the restoration, with a resultant diffused discoloration that spreads from the involved margin. Another rare occurrence is the cohesive failure of either the tooth or the porcelain. In the first instance, the fracture of the underlying tooth is usually the result of poor judgment in selection of the tooth to be veneered. Vital anterior teeth with large existing restorations on the mesial and distal surfaces and nonvital anterior teeth might be better served with full-coverage porcelain restorations bonded to the additional surface area of the crown preparation on dentin. A more common problem is the cohesive failure of the porcelain itself, which may occur during cementation as a result of a poor-fitting restoration, a resin that is too thick (viscous), or a resin that has gone through some initial setting. The latter can result if the resin is left too long in ambient light or unit light. Cohesive failure also may occur after cementation as the result of poorly planned occlusion or traumatic injury.